Pengaruh Gaya Kepemimpinan Demokratis Terhadap Kinerja Karyawan Yang Dimediasi Oleh Kepuasan Kerja (Studi Karyawan Yayasan Pendidikan Islam Hidayatul Mubtadi’in Tasikmadu, Malang). - Anan, Nurun Nadiva Salsabila; Mardani, Ronny Malavia; Amin, Muhammad Sirojuddin (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research aims to analyze the influence of democratic leadership style on employee performance with job satisfaction as a mediating variable. The object of this research is employees at the Hidayatul Mubtadi'in Islamic Education Foundation in Tasikmadu, Malang. The research approach used is quantitative with an explanatory research method. Data was collected through questionnaires distributed to 57 respondents, consisting of teachers and foundation employees. The data analysis technique uses Structural Equation Modeling (SEM) with the help of SmartPLS 3.0 software.The research results show that democratic leadership style has a significant influence on job satisfaction and employee performance. In addition, job satisfaction has been proven to act as a mediating variable in the relationship between democratic leadership style and employee performance. Thus, the higher the application of democratic leadership, the greater the increase in job satisfaction which has implications for increasing employee performance. These findings contribute to human resource management in the Islamic education environment and become a reference for developing leadership policies in educational organizations. Keywords: Democratic Leadership Style, Employee Performance, Job Satisfaction, Islamic Education Foundation, SEM-PLS